(untitled) (Proceedings of International Educators Conference, 2023)
The scientific article discusses some of the issues of youth in the education system, since youth is our future, the more enlightened, cultural and spiritually mature it is, the brighter our future will be.Each rising generation should be educated, well-read, brought up.